PEMAHAMAN DAN TANTANGAN WAJIB PAJAK DALAMUMKM DI ERA DIGITAL - AHMAD MU’TI LABIB; DWI KOERNAWATI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
Tax is the main source of state revenue which is very important in financing national development. Micro, Small, and Medium Enterprises (MSMEs) play a major role in the Indonesian economy, but their tax compliance rate is still low. In the digital era, the government has introduced a digital taxation policy to improve the efficiency and reach of the taxation system. This study uses a qualitative approach through literature studies to examine the understanding and challenges of MSME taxation in the digital era. The results show that although digitalization offers various benefits such as transparency and wider market access, MSMEs face challenges in the form of minimal digital literacy, technological limitations, and resistance to change. Support in the form of training, incentives, and inclusive policies is needed so that MSMEs can be integrated into the digital taxation system effectively and sustainably